2016
DOI: 10.1177/0042098015613206
|View full text |Cite
|
Sign up to set email alerts
|

Struggles to form business improvement districts (BIDs) in Los Angeles

Abstract: Autonomous efforts to improve local business environments have become an increasingly important impetus for economic development. Business improvement districts (BIDs), as one of such autonomous organisations, have clearly demonstrated benefits for promoting commercial areas over the last two decades. When BIDs spread over a city, however, not every commercial district succeeds in establishing BIDs despite some initial efforts. This research examines the types of challenges that these neighbourhoods experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, Cidell (2015) finds that airports are not necessarily stronger generators of economic development compared to other major municipal infrastructures. Airport investments may simply hasten growth that would have occurred anyways rather than generating new growth, similar to local business incentives (Wassmer 1994; Lee 2015).…”
Section: Why Use the Airport For Growth?mentioning
confidence: 99%
“…However, Cidell (2015) finds that airports are not necessarily stronger generators of economic development compared to other major municipal infrastructures. Airport investments may simply hasten growth that would have occurred anyways rather than generating new growth, similar to local business incentives (Wassmer 1994; Lee 2015).…”
Section: Why Use the Airport For Growth?mentioning
confidence: 99%
“…The importance of the characteristics of each area is to be seen, not only in the international transfer. To this matter, Lee [105] argues that BIDs may not work in all areas. For instance, in some areas, businesses may not be in decline and, consequently, their owners may not think it is necessary to run a BID project in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis (2010) observed that BIDs can be successful in promoting urban revitalization, however they concurrently pose concerns that include intensifying socioeconomic and spatial inequalities, weakening municipal government, and restricting democratic accountability. It has also been shown that there is particular difficulty establishing BIDs in economically challenged areas and neighborhoods with large immigrant populations (Lee 2016), reflecting how wealthier neighborhoods may be at a particular advantage for successfully implementing the BID model.…”
Section: Business Improvement Districts: Boost or Barrier?mentioning
confidence: 99%